1988
DOI: 10.1126/science.3336776
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Human Immunodeficiency Virus (HIV-1) Infection Among Laboratory Workers

Abstract: In a prospective cohort study of 265 laboratory and affiliated workers, one individual with no recognized risk factors for human immunodeficiency virus type 1 (HIV-1) infection was HIV-1 seropositive at the time of entry into the study. Molecular analyses of two HIV-1 isolates derived in two independent laboratories from a blood sample from this worker showed that the isolates were indistinguishable from a genotypic form of HIV-1 present in the H9/HTLV-IIIB cell line. Exposure to this strain of virus most prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0
4

Year Published

1989
1989
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(72 citation statements)
references
References 12 publications
2
66
0
4
Order By: Relevance
“…Because of these differences, and to highlight the fact that these workers were exposed to the IIIB stock, we will subsequently refer to the infecting strain of virus as HIV-1 IIIB. Subject LWF was infected in 1985, but the event that caused the infection has not been defined (21). LWF developed AIDS in 1993 as the CD4 count dropped below 200 cells/mm 3 (22) and in July 1995 the CD4 count was 190 cells/mm 3 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of these differences, and to highlight the fact that these workers were exposed to the IIIB stock, we will subsequently refer to the infecting strain of virus as HIV-1 IIIB. Subject LWF was infected in 1985, but the event that caused the infection has not been defined (21). LWF developed AIDS in 1993 as the CD4 count dropped below 200 cells/mm 3 (22) and in July 1995 the CD4 count was 190 cells/mm 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant vaccinia viruses expressing the Gag, RT, and Env genes from molecular clones (BH8, BH10, PV22) derived from the HIV-1 IIIB strain were used to express viral antigens on target cells. Recombinant vaccinia viruses expressing serial truncations of the HIV-1 envelope glycoprotein (vPE 16,17,18,20,21,22) were constructed from the BH8 molecular clone of HIV-1 (26,27). For the mapping of Env epitopes, we also used vaccinia viruses expressing serial deletions of the HIV-1 BH10 Env (vAbt 271, 299, 294, 295, 296, provided by Dr. Dennis Panicali, Therion Biologics, Cambridge, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Goh and colleagues (Goh et al, 1998) performed a retrospective, longitudinal analysis of the vpr gene sequence in this animals virus populations, which revealed restoration of the truncated open reading frame in both chimpanzees at 6 to 8 weeks and at 2 years post-inoculation, respectively (Goh et al, 1998). The second study resulted from an unfortunate accident in which a laboratory worker became infected with a stock of HIV IIIB , which also contained the above inactivating mutation in vpr (Reitz et al, 1994;Weiss et al, 1988). Sequence analysis of virus from peripheral blood cells from this individual two years after infection revealed that the vpr gene reverted to full-length (Goh et al, 1998).…”
Section: Vpr Sequence Variationmentioning
confidence: 99%
“…LW1 was isolated from an HIV-1 IIIB -infected lab worker and is genetically similar to HIV-1 IIIB isolated from the H9/HTLV-IIIB cell line, with the exception that LW1 is dual tropic (20). Virus was injected into mice as before and harvested for rescue experiments after 3 wk in vivo.…”
Section: Figurementioning
confidence: 99%